Numerical computation of depth of buried geologic structure from the gravity anomaly data - Rahman, Syed Mustafizur (GEOLOGICAL SOCIETY OF MALAYSIA, 2011)
Introduction: The gravity anomaly interpretation is mostly done by iterative methods. Iterations start to compute gravity anomaly for a model with few known geologic parameters. Computed gravity anomaly is compared with the observed values and sometimes the model needs to be modified in order to obtain reasonable agreement. Several methods have been developed to identify the shape (Sharma & Geldart, 1968; Abdelrahman & El-Araby, 1993;Salem et al., 2003) and depth (Abdelrahman, 1990; Elawadi et al., 2001) of geological structure assuming simple source geometry from gravity data, though the simple geometries are not geologically realistic in most of the cases. In many contributions, numerical methods have been presented the estimation of depths of the geological structures of the gravity anomalies. This research is also introduced a numerical approach to estimate depths of simple models from residual gravity anomaly.